Pemodelan Farmakofor untuk Identifikasi Inhibitor Heat Shock Proteins-90 (HSP-90): Pharmacophore Modeling to Identify Heat Shock Proteins-9 (HSP-90) Inhibitors - Arba, Muhammad; Arfan; Trisnawati, Ayu; Kurniawati, Desi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Heat shock proteins-90 (HSP-90) is a protein that plays an important role in the life cycle of normal and cancer cells for their self protection from thermal stress, oxidative damage, and cell hypoxia. Inhibition of HSP90 is one way to suppress the growth of cancer cells. In this study, pharmacophore modeling and molecular docking were conducted to identify hit compounds as inhibitors of HSP-90. The pharmacophore feature consists of three hydrogen bond acceptors, one hydrogen bond donor and one hydrophobic feature with Area Under Curve of Receiver Operating Characteristics (AUCROC) is 0.5 and the Goodness of Hit (GH) value is 0.752. Screening in the ZINC database generated 1,500 hit compounds, were subjected to molecular docking to determine their binding energy and interactions with HSP-90. The range of binding energy (E) of all hit compounds is -5.68 to -12.24 kcal/mol and there are four best hit compounds namely lig_543, lig_527, lig_1337 and lig_337, when compared to native ligands (PU2, E=-8.25 kkal/mol) based on the binding energy and orientation, which indicate their potential as new HSP-90 inhibitors.